Early impact of COVID-19 pandemic on paediatric surgical practice in Nigeria: a national survey of paediatric surgeons - Ibukunolu Olufemi Ogundele; Felix M Alakaloko; Collins C Nwokoro; Emmanuel A Ameh (BMJ Publishing Group, 2020)
Introduction The novel coronavirus disease has had significant impact on healthcare globally. Knowledge of this virus is evolving, definitive care is not yet known and mortality is increasing. We assessed its initial impact on paediatric surgical practice in Nigeria, creating a benchmark for recommendations and future reference.Methods Survey of 120 paediatric surgeons from 50 centres to assess sociodemographics and specific domains of impact of COVID-19 on their services and training in Nigeria. Valid responses were represented as categorical data and presented in percentages. Duplicate submissions for centres were excluded by combining and taking the mean of responses from centres with multiple respondents.Results Response rate was 74 (61%). Forty-six (92%) centres had suspended elective surgeries. All centres continued emergency surgeries but volume reduced in March by 31%. Eleven (22%) centres reported 13 suspended elective cases presenting as emergencies in March, accounting for 3% of total emergency surgeries. Twelve (24%) centres adopted new modalities for managing selected surgical conditions: non-operative reduction of intussusception in 1 (2%), antibiotic management of uncomplicated acute appendicitis in 5 (10%) and more conservative management of trauma and replacement of laparoscopic appendectomy with open surgery in 3 (6%), respectively. Low perception of adequacy of personal protective equipment (PPE) was reported in 35 (70%) centres. Forty (80%) centres did not offer telemedicine for patients' follow-up. Twenty-nine (58%) centres had suspended academic training. Perception of safety to operate was low in 37 (50%) respondents, indifferent in 24% and high in 26%.Conclusion Majority of paediatric surgical centres reported cessation of elective surgeries while continuing emergencies. There was, however, an acute decline in the volume of emergency surgeries. Adequate PPE needs to be provided and preparations towards handling backlog of elective surgeries once the pandemic recedes. Further study is planned to more conclusively understand the full impact of this pandemic on children's surgery.